The impact of abstinence from chronic alcohol consumption on the mouse striatal proteome: sex and subregion-specific differences - Duffus, Brittnie-lee M.; Haggerty, David L.; Doud, Emma H.; Mosley, Amber L.; Yamamoto, Bryan K.; Atwood, Brady K. (Frontiers in Pharmacology, 2024)
Alcohol misuse is the third leading preventable cause of death in the world. The World Health Organization currently estimates that 1 in 20 deaths are directly alcohol related. One of the ways in which consuming excessive levels of alcohol can both directly and indirectly affect human mortality and morbidity, is through chronic inflammation. Recently, studies have suggested a link between increased alcohol use and the incidence of neuroinflammatory-related diseases. However, the mechanism in which alcohol potentially influences neuroinflammatory processes is still being uncovered. We implemented an unbiased proteomics exploration of alcohol-induced changes in the striatum, with a specific emphasis on proteins related to inflammation. The striatum is a brain region that is critically involved with the progression of alcohol use disorder. Using mass spectrometry following voluntary alcohol self-administration in mice, we show that distinct protein abundances and signaling pathways in different subregions of the striatum are disrupted by chronic exposure to alcohol compared to water drinking control mice. Further, in mice that were allowed to experience abstinence from alcohol compared to mice that were non-abstinent, the overall proteome and signaling pathways showed additional differences, suggesting that the responses evoked by chronic alcohol exposure are dependent on alcohol use history. To our surprise we did not find that chronic alcohol drinking or abstinence altered protein abundance or pathways associated with inflammation, but rather affected proteins and pathways associated with neurodegeneration and metabolic, cellular organization, protein translation, and molecular transport processes. These outcomes suggest that in this drinking model, alcohol-induced neuroinflammation in the striatum is not a primary outcome controlling altered neurobehavioral function, but these changes are rather mediated by altered striatal neuronal structure and cellular health.